Policies on sexual expression in forensic psychiatric settings in different European countries - Tiwana, Rajveer; McDonald, Stephanie; Völlm, Birgit (BioMedCentral, 2016)
Background: Sexual expression by forensic psychiatric patients is poorly researched. Methods: Forensic experts representing 14 European countries were interviewed to explore the diverse ways in which sexual expression within forensic settings is handled. Results: No country had a national policy, although many had local policies or shared practices. Progressive approaches to patient sexuality were evident in nine of the countries sampled. The UK appeared the most prohibiting and excluding, its protocols apparently based on risk aversion and lack of emphasis or consideration of patients’ sexual needs. Conclusions: Uniform national policy supporting patients’ sexual expression would provide significant improvements.